Designing fiscal redistribution - Coady, David,Le, Nghia-Piotr (International Monetary Fund, 2020)
There is a growing debate on the relative merits of universal and targeted social assistance transfers in achieving income redistribution objectives. While the benefits of targeting are clear, id est, a larger poverty impact for a given transfer budget or lower fiscal cost for a given poverty impact, in practice targeting also comes with various costs, including incentive, administrative, social and political costs. The appropriate balance between targeted and universal transfers will therefore depend on how countries decide to trade-off these costs and benefits as well as on the potential for redistribution through taxes. This paper discusses the trade-offs that arise in different country contexts and the potential for strengthening fiscal redistribution in advanced and developing countries, including through expanding transfer coverage and progressive tax financing
10.5089/9781513547046.001
Keywords: Graue Literatur; Taxation; Poverty and Homelessness; Distribution: General; Efficiency; Optimal Taxation; National Government Expenditures and Welfare Programs; Personal Income; Wealth; and Their Distributions; Aggregate Factor Income Distribution; Taxation; Subsidies; and Revenue: General; Welfare; Well-Being; and Poverty: General; Macroeconomics; Public finance & taxation; Poverty & precarity; Personal income; Income tax systems; Fiscal redistribution; Income inequality; National accounts; Taxes; Income; Income distribution; Income tax; Poverty; transfers; taxes; targeted; universal